Description of Blood Sugar Levels in Medical Student of Universitas Prima Indonesia - Cindy Fangesty; Wienaldi (HM Publisher, 2021)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia. Various epidemiological studies have shown an increasing trend in the incidence and prevalence of diabetes mellitus in various parts of the world. Lifestyle changes lead to an increasing prevalence of metabolic syndrome diabetes mellitus. This study aims to determine the description of blood sugar levels during class 2017 students of the Faculty of Medicine, Prima Indonesia University. This type of observational analytic research with sampling techniques using non-methods This research is a descriptive study with a cross-sectional study design. This research will be carried out at the UNPRI campus building 1. The sample of this study is all medical students of the 2017 Prima Indonesia University class totaling 99 people. Data were collected using a questionnaire and analyzed by univariate. The results showed that the majority of the respondents were female, namely 66 people (66.7%), while only 33 male respondents (33.3%) were male respondents. According to blood sugar levels, all respondents had normal blood sugar levels (100%). Respondents are advised to maintain a healthy diet and lifestyle so that their blood sugar levels remain stable and ultimately avoid the risk of diabetes mellitus.